2020
DOI: 10.1186/s40643-020-00337-3
|View full text |Cite
|
Sign up to set email alerts
|

Influence of culture conditions on the production of extracellular polymeric substances (EPS) by Arthrospira platensis

Abstract: Arthrospira platensis is a cyanobacterium that is of great biotechnological interest, particularly for the food industry, as it possesses a high content of proteins, pigments, lipids and carbohydrates. Cyanobacteria produce extracellular polymeric substances (EPS), which are co-products of secondary metabolism that present thickening or gelling properties. A 3-level factorial design was used to study the combined effect of different nitrate concentrations and photon flux density (PFD) values to evaluate the bi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 51 publications
(67 reference statements)
3
7
0
Order By: Relevance
“…The data also show high variations between the ratios of the individual components and a clear dependency between the obtained product and the extraction technique used, which makes a standardized production process necessary. These findings are in accordance with several other studies, confirming that changes in culture conditions can influence the release and molecular composition of microalgae metabolites [ 89 , 90 , 91 ]. It is a common practice to induce the biosynthesis of target metabolites, such as pigments, EPS and lipids by changes in nutrient, salinity and light availability [ 22 , 69 , 74 , 92 , 93 , 94 ].…”
Section: Discussionsupporting
confidence: 93%
“…The data also show high variations between the ratios of the individual components and a clear dependency between the obtained product and the extraction technique used, which makes a standardized production process necessary. These findings are in accordance with several other studies, confirming that changes in culture conditions can influence the release and molecular composition of microalgae metabolites [ 89 , 90 , 91 ]. It is a common practice to induce the biosynthesis of target metabolites, such as pigments, EPS and lipids by changes in nutrient, salinity and light availability [ 22 , 69 , 74 , 92 , 93 , 94 ].…”
Section: Discussionsupporting
confidence: 93%
“…Li et al [ 44 ] found that P. purpureum exhibited the highest EPS content when cultured at low initial nitrogen concentrations (3.5 mM). Silva et al [ 45 ] reported that the best EPS yield in A. platensis was achieved under the lowest NaNO 3 concentration (0.25 g L −1 ). Additionally, Cepák and Přibyl [ 46 ] demonstrated that the most abundant EPS levels in B. braunii were produced at a moderate nitrogen concentration of 6 mM.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, there is a positive effect of high light intensity on EPS (Delattre et al, 2016). When comparing different reports, one could conclude that EPS production is enhanced at low irradiations by increasing the light supply, leading to a light inhibition at high light intensities (Trabelsi et al, 2009;Delattre et al, 2016;Silva et al, 2020). The optimum light supply strongly depends on the production organism (Trabelsi et al, 2009;Silva et al, 2020) and the reactor system (Iqbal and Zafar, 1993).…”
Section: Introductionmentioning
confidence: 99%